STATUS DAN IDENTITAS SOSIAL SAUDAGAR BATIK LAWEYAN DALAM INTERIOR DALEM INDIS DI AWAL ABAD KE-20 - Dhian Lestari Hastuti (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2011)
The article is the research result dealing with the bearing process and interior visual structure of internal house (dalem) in the house of the Laweyan Batik merchant in Surakarta-Central Java at the early of 20th century. In this time, the interior of internal house (dalem) for Laweyan society is a status symbol and social identity because they are part of the marginal society in social life. The success in managing the business of printing batik does not move up their social class from lowerclass to upper class (priyayi). Their profession as seller places them in lower-class (kawula). The internal house (dalem) context as part of heritage building in order to get social status and identity is toughened by historical and cultural approaches. Those approaches able to explain how the cultural system forms a social system, then, it actualizes in the form of culture: artefact of internal house (dalem) in the house of batik’s merchant. The conclusion of the research is the Laweyan Batik merchants have experienced metamorphosis from the lawe market society into an exclusive Batik Village. The sharing system of social class which has done by Dutch government, empire, or urban development based on the ethnicity has a role in parallelizing the Laweyan Batik merchant with priyayi belonging to upper class. The merchants place the internal house (dalem) as sacred area as the form of their fighting in creating the self identity. The transformation is influenced by a blueprint measurement which refers to loji building design. The sacredness of the area is kept even though it is without mancapat pattern. The function displacement happens because of need adjustment of places of the merchants. The interior design of internal house (dalem) supported by symbolism in Javanese culture and modern Europe style, Art Nouveau, and Art Deco is as the form of acculturation of visual design giving solution in shaping the social identity of the merchants. Keywords: Internal house, marginal, identity, merchants of batik Laweyan-Surakarta